Anxious and Angry: Emotional Responses to the COVID-19 Threat - Abadi, David; Arnaldo, Irene; Fischer, Agneta (Frontiers in Psychology, 2021)
The current COVID-19 pandemic elicits a vast amount of anxiety. In the current study, we investigate how anxiety related to COVID-19 is associated with support for and compliance with governmental hygiene measures, and how this is influenced by populist attitudes, anger at the government and conspiracy mentality. We conducted an online survey in April 2020 in four different countries (Germany, the Netherlands, Spain and the UK; N=2031), using a cross-sectional design. Results showed that (1) anxiety related to COVID-19 is associated with conspiracy beliefs, anger at the government and populist attitudes, and (2) support for and compliance with hygiene measures are both positively predicted by anxiety related to COVID-19, however, (3) support for hygiene measures is also predicted by populist attitudes, and negatively by conspiracy mentality, whereas compliance with hygiene measures is more strongly predicted by anger at transgressors (anger at people transgressing the hygiene measures). Consequently, although anxiety related to COVID-19 concerns one’s health, it has also political and social implications: anxiety is associated with an increase in anger, either at transgressors or at the government.